Comparative Genomic Analysis of Agarolytic Flavobacterium faecale WV33T - Lee, Jun Ho; Lee, Seong Rae; Han, Sejong; Lee, Pyung Cheon (International Journal of Molecular Sciences, 2022)
Flavobacteria are widely dispersed in a variety of environments and produce various polysaccharide-degrading enzymes. Here, we report the complete genome of Flavobacterium faecale WV33T, an agar-degrading bacterium isolated from the stools of Antarctic penguins. The sequenced genome of F. faecale WV33T represents a single circular chromosome (4,621,116 bp, 35.2% G + C content), containing 3984 coding DNA sequences and 85 RNA-coding genes. The genome of F. faecale WV33T contains 154 genes that encode carbohydrate-active enzymes (CAZymes). Among the CAZymes, seven putative genes encoding agarases have been identified in the genome. Transcriptional analysis revealed that the expression of these putative agarases was significantly enhanced by the presence of agar in the culture medium, suggesting that these proteins are involved in agar hydrolysis. Pangenome analysis revealed that the genomes of the 27 Flavobacterium type strains, including F. faecale WV33T, tend to be very plastic, and Flavobacterium strains are unique species with a tiny core genome and a large non-core region. The average nucleotide identity and phylogenomic analysis of the 27 Flavobacterium-type strains showed that F. faecale WV33T was positioned in a unique clade in the evolutionary tree.
Keywords: Agar; DNA, Bacterial; Fatty Acids; Flavobacteriaceae; Flavobacterium; Genomics; Nucleotides; Phylogeny; Plastics; RNA; RNA, Ribosomal, 16S; Sequence Analysis, DNA; agarase; CAZymes; comparative genomics; Flavobacterium faecale